(Research on the preparation of fermented cassava flour. I.effects of Fermentation and Drying Methods on the Quality of Gari) - Basrah Enie, A.; Budi Wahyuningsih, Sri; -, Sardjono; Hartoto, Liesbetini (Warta Industri Hasil Pertanian, 1992)
Research on the preparation of fermented cassava flour,gari,has been conducted.The cassava varieties used were Adira 1 and Adira IV.The cassava pulp were fermentedby a traditional method for 2,3,and 4 days.The drying methods used were sun drying,oven drying,and roasting.Changes in moisture contents,ash,total titratable accidity,protein content degree of whiteness and flavour of gari flour were observed.good quality gari flour can be obtained from Adira IV variety which was fermented for 3 days and dried by roasting.The moisture content,acidity and degree of whitness of product were 13.2%,0.72%, and 80.9%,respectively.